Phase II Trial of Maintenance Treatment With IL2 and Zoledronate in Multiple Myeloma After Bone Marrow Transplantation: Biological and Clinical Results - Fazzi, Rita; Petrini, Iacopo; Giuliani, Nicola; Morganti, Riccardo; Carulli, Giovanni; Dalla Palma, Benedetta; Notarfranchi, Laura; Galimberti, Sara; Buda, Gabriele (Frontiers in Immunology, 2021)
Background: Maintenance treatment after autologous bone marrow transplantation in multiple myeloma improves the outcome of patients. We designed a phase II clinical trail to evaluate the treatment with IL2 and zoledronate after autologous bone marrow transplantation in myeloma patients. Methods: Patients, with a histologically proven diagnosis of multiple myeloma become eligible if achieved a very good partial remission in bone marrow samples after 3 months from autologous bone marrow transplantation. IL2 was administered from day 1 to 7. In the first cycle, the daily dose was 2 x 106 IU, whereas, in subsequent ones the IL2 dose was progressively escalated, with + 25% increases at each cycle, until evidence of toxicity or up to 8 x 106 IU. Four mg of zoledronic acid were infused on day 2. Flow cytometry analysis of  lymphocytes was preformed at day 1 and 8 of treatment cycles. Results: 44 patients have been enrolled between 2013 and 2016. The median time to progression was 22.5 months (95%CI 9.7-35.2). A complete remission with a negative immunofixation was obtained in 18% of patients and correlated with a significantly longer time to progression (p=0.015). Treatment was well tolerated without G3 or 4 toxicities. After a week of treatment with IL2 and zoledronate, γδ lymphocytes, Vγ9δ2, CD57+, effector, late effector and memory γδ increased but in subsequent cycles, there was a progressive reduction of this expansion. Conclusions: The maintenance treatment with IL2 and Zoledronate is feasible and possibly active in multiple myeloma patients after autologous bone marrow transplantation.